Policies and innovations to battle Covid-19 – A case study of South Korea. Issue 4 (December 2020) - Lee, Doowon; Choi, Bobae
Highlights: Fast government response to legislate new laws to protect health care workers prevented human capital loss. General public preferred transparent information over privacy which provided grounds for the government to implement innovative movement tracking systems. Utilizing non-hospital facilities for patients needing minor to no treatment as isolation facilities reduced the stress on the medical system. Innovation on how the testing facilities are designed, such as the drive through testing method, has now been adapted by other coutries. Abstract: Objectives: To describe how health care crisis resulting from the COVID-19 pandemic in South Korea has led to innovation and changes to government policy. This paper presents the significant cluster events, relevant developments of innovation, and economical impact in Korea that could inform policy makers on how to respond to health crises in the future. Methods: Health care, economy, epidemiological data are collected from various sources including the Korea Centers for Disease Control and Prevention (KCDC) or other government sources. Results: The KCDC jointly with medical professionals developed a series of innovations such as 1) Full contact tracing and rapid testing with a 12 h turnaround and 10 min movement tracking systems, 2) transparent disclosure of all contract tracing data to the public through a central database, 3) Drive-Through and Walk-Through testing methods, and 4) a 4 tier patient severity index and community treatment isolation centers. Korea moved from the 4th in the world for total confirmed cases in March down to 76th in August. Conclusions: Expedited enforcement of amended legislation acts to protect the healthcare workforce resulted in only 10 healthcare professionals contracting the virus while caring for Covid-19 patients. This has resulted in minimal human capital loss and the government was able to re-direct existing medical workforce to areas in need. The quarantine strategies implemented resulted in little need to lock down the whole economy but also limited the cost spent to gain a year of life to 193, 848 Won (US$163).